Nurses' Compliance with Hospital Accreditation Standards During Patient Admission in Intermediate Care: An Observational Study - Fauziyatul Fitriyah; Kholid Rosyidi Muhammad Nur; Ahmad Rifai; Masmuhul Khoir (KHD Production, 2026)
Patient admission is a critical phase in hospital services, particularly in semi-intensive units such as the High Care Unit (HCU), where patient safety and continuity of care must be ensured from the initial point of contact. Nurses play a central role in conducting initial screening, coordinating care, and ensuring compliance with hospital accreditation standards. This study aimed to describe the role of nurses in admitting new patients to the High Care Unit (HCU) Melati at Bangil Regional General Hospital based on the Access to Care and Continuity of Care (AKP) 1.2 standard of the Indonesian National Hospital Accreditation (SNARS) 2022. A descriptive case study design was used. Data were collected through direct observation using a checklist adapted from the AKP 1.2 SNARS 2022 instrument. Five nurses working in the HCU were selected through purposive sampling. Data analysis was conducted descriptively using frequency distributions and percentages.The results showed that all nurses demonstrated good performance in implementing the AKP 1.2 standard during the patient admission process, with 100% of respondents categorized as good. High compliance was observed in patient admission criteria, coordination of care, and documentation. However, minor gaps were identified in comprehensive initial assessment and role distribution during periods of high workload. In conclusion, the role of nurses in admitting new patients to the HCU Melati has been implemented in accordance with the AKP 1.2 SNARS 2022 standard. Continuous supervision, clear role allocation, and managerial support are recommended to maintain consistency and further enhance patient safety and quality of care in semi-intensive units.